Reaction Products in the Combustion of the High Energy Density Storage Material Lithium with Carbon Dioxide and Nitrogen. Issue 1644 (14th March 2014) - Kellermann, Renate; Taroata, Dan; Schiemann, Martin; Eckert, Helmut; Fischer, Peter; Scherer, Viktor; Hock, Rainer; Schmid, Guenter
ABSTRACT In this work, electrochemically recyclable lithium is analyzed as high energy density, large scale storage material for stranded renewable energy in a closed loop. The strongly exothermic reaction of lithium with carbon dioxide (CO2) yields thermal energy directly comparable to the combustion of coal or methane in an oxygen containing atmosphere. The thermal level of the reaction is sufficient for re-electrification in a thermal power plant compatible process. The reaction of single lithium particles, avoiding particle-particle interactions, is compared to the combustion of atomized lithium spray in a CO2 containing atmosphere. Particle temperatures of up to 4000K were found for the reaction of single lithium particles in a CO2, nitrogen (N2), oxygen (O2) and steam gas mixture. Furthermore the combustion of atomized lithium spray in both dry CO2 atmosphere and CO2/steam gas mixture was analyzed. The identified solid reaction products are lithium carbonate, lithium oxide and lithium hydroxide. The formation of carbon monoxide (CO) as gaseous reaction product is demonstrated. Carbon monoxide is a valuable by-product, which could be converted to methanol or gasoline using hydrogen.